IMPROVEMENT OF STUDENT LEARNING OUTCOMES IN PHYSICS USING CASE STUDY METHOD - Pretti TM Ambarita; Ridwan Abdullah Sani (UNIVERSITAS NEGERI MEDAN, 2013)
Abstract This research was carried outto study student learning outcomes using case study and conventional method and its comparison using both ofmethods.The problem of conventional class with teacher-centered learning are: 1) student doesn’t understand how to connect physics concept in technology and daily life, 2) student can not solve contextual physics problems, 3) critical thinking is not developed. Case study method was choosen in this study in order to develop student critical thinking and their ability to solve contextual physics problems. Experimental research method using experiment and control class was conducted in this study. Research shows that the student learning outcomes using the case study is better than conventional method.. Key Word :casestudy, critical thinking, physics, learning outcomes, static fluid